PENGGUNAAN JUMPUTAN , TRITIK DALAM UPACARA ADAT DI SURAKARTA - sarwono, sarwono -; Josef, Adji Isworo; Affanti, Tiwi Bina; Santoso, Ratna Endah; Wahyuningsih, Novita (Institut Seni Indoensia Surakarta, 2021)
ABSTRACTThe Javanese society has a harmony concept which has become an interesting tradition part in live. The Javanese people, especially the Surakarta society, have a belief in the world philosophy (universe), consisting of the great universe ( macrocosmos) and small universe ( microcosmos). The microcosmos cannot be separated from the great macrocosmos which must be kept its harmony with their lives, so the ritual elements of the small universe. Therefore, the art isi always connected with their lives, so the ritual elements consist in the traditional art. The art has three functions known in Javanese society, that is for a ritual purpose and a show purpose with entertaining characteristics for the inner satisfaction in the society. Moreover, the traditional artwhich is formed in the usage art, like the custom clothes, tools / instruments, ornaments and others functioning as ritual purposes, have definitely had the important value symbols in the society, or as the tools to support the ritual implementation in the society.The art of Tritik and Jumputan craft also contains the teachings of ethics and aesthetics in the form of visual appearances and symbolism of life which can basically lead humans to perfection and true identity.Keywords: Jumputan,Tritik, The custom ceremony, traditional ABSTRAKMasyarakat Jawa memiliki konsep keselarasan yang merupakan bagian tradisi yang penting dalam kehidupan. Orang Jawa, khususnya masyarakat Surakarta memiliki keyakinan dalam pandangan dunia (jagat), yang terdiri dari jagat gede (makrokosmos) dan jagat cilik (mikrokosmos). Mikrokosmos menjadi yang tidak terpisahkan dengan makrokosmos yang harus dijaga keselarasannya dengan unsur-unsur jagat cilik. Oleh sebab itu, seni selalu dikaitkan dengan kehidupannya, sehingga unsur ritual terdapat dalam seni tradisional. Kesenian memiliki tiga fungsi yang dikenal dalam masyarakat Jawa, yaitu untuk tujuan ritual, untuk tujuan tontonan yang bersifat entertaintment kepuasan batin dalam masyarakat. Apalagi kesenian tradisional yang berbentuk seni pakai, seperti pakaian adat, peralatan, hiasan, dan sebagainya dalam fungsinya sebagai kepentingan ritual, sudah barang tentu memiliki simbol-simbol yang bernilai dalam masyarakat, ataupun sebagai sarana untuk mendukung pelaksanaan ritual dalam masyarakat. Seni kerajinan tritik dan jumputan ini juga termuat ajaran etika dan keindahan yang berbentuk penampilan visual dan simbolisme hidup yang pada dasarnya dapat menuntun manusia menuju kesempurnaan dan jati diri yang sejati.Kata kunci : Jumputan, Tritik, Pakaian Adat, Tradisional